Diseño de un plan de mejoramiento para la gestión administrativa de la empresa Puntomerca Merchandisng sede Santiago de Cali (2013)
The main purpose of this project is to determine the external and internal variables in the company headquarters Puntomerca Merchandising Cali, in order to identify existing gaps in the administrative process and propose strategies to achieve improvement. To achieve the objectives the exploratory methodology was used , were investigated in company documents for they know their history , mission, vision , policies and corporate values ; Description for the steps to perform the matrices are mentioned which were analyzed key success factors of the company in order to identify opportunities for improvement if they are to the organization. Interview which the commercial executives at headquarters and finally the matrices used strategic planning to identify factors, such as survey instruments which are applied externally to potential clients and internally based administrative director were used keys to success. This allowed propose improvement strategies to overcome the shortcomings found by improving the efficiency of the site, optimizing their processes and ensure their sustainability overtime.